Penerapan Aplikasi Sicantik Cloud Terhadap Pelayanan di DPMPTSP Banda Aceh - Hanivi Yanti; Sri Wahyu Handayani (Sawala : Jurnal Administrasi Negara, 2022)
E-government has become the most important thing in a government agency to support the progress of the agency and improve services. DPMPTSP Banda Aceh then launched the SiCantik Cloud application created by the Ministry of Communication and Information to make it easier to manage permits. The SiCantik Cloud application is an innovation of licensing and non-licensing services with an online system. This study aims to analyze the impact of the SiCantik Cloud application on services and to find out the obstacles that occur during its implementation. This study uses a qualitative descriptive method conducted at the DPMPTSP Banda Aceh, Aceh Province. Collecting data through interviews, observation, and documentation. Determination of informants using purposive sampling and accidental sampling methods. The data were analyzed by means of reduction, data presentation and drawing conclusions. The results of the study indicate that the implementation of the SiCantik application at the Banda Aceh DPMPTSP is quite good and effective, where users of the SiCantik Cloud application, both employees and the community, are greatly helped both in terms of service which is easy and fast. However, the network is still lacking because the traffic load is too high, so the application is often slow and has errors. Then there are also people who have not been able to access the application due to lack of understanding and no face-to-face socialization by the manager. The data information generated is trusted and data security is maintained (trusted), users and beneficiaries strongly support the use of this beautiful application. So it can be concluded that although there are still various obstacles in the use of this application, they do not have a big impact on the effectiveness, transparency, accountability, and efficiency in the use of the SiCantik Cloud application at the Banda Aceh DPMPTSP.